2024
DOI: 10.3389/fnagi.2024.1389454
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in the brain–lung crosstalk: cellular and molecular perspectives

Jianda Kong,
Rao Fan,
Yuanqi Zhang
et al.

Abstract: Oxidative stress is caused by an imbalance between the production of reactive oxygen species (ROS) and the body’s ability to counteract their harmful effects, playing a key role in the pathogenesis of brain and lung-related diseases. This review comprehensively examines the intricate mechanisms by which oxidative stress influences cellular and molecular pathways, contributing to neurodegenerative, cardiovascular, and respiratory disorders. Emphasizing the detrimental effects on both brain and lung health, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 124 publications
0
0
0
Order By: Relevance
“…Overall, these findings underscore the importance of monitoring MDA levels as a marker for oxidative stress and its potential implications in biological systems (Bencivenga et al, 2023;Wróbel-Nowicka et al, 2024;Kong et al, 2024;Valavanidis et al, 2006). Further research may delve into elucidating the specific factors contributing to the observed increase in MDA levels in the control (+) group, leading to a better understanding of the underlying mechanisms and potential therapeutic interventions to mitigate oxidative stress-related damage.…”
Section: Figure 1 Mda Standard Curvementioning
confidence: 74%
“…Overall, these findings underscore the importance of monitoring MDA levels as a marker for oxidative stress and its potential implications in biological systems (Bencivenga et al, 2023;Wróbel-Nowicka et al, 2024;Kong et al, 2024;Valavanidis et al, 2006). Further research may delve into elucidating the specific factors contributing to the observed increase in MDA levels in the control (+) group, leading to a better understanding of the underlying mechanisms and potential therapeutic interventions to mitigate oxidative stress-related damage.…”
Section: Figure 1 Mda Standard Curvementioning
confidence: 74%